Expression of the K-fgf proto-oncogene is controlled by 3' regulatory elements which are specific for embryonal carcinoma cells. - Curatola, A M (1990)
Expression of the K-fgf/hst proto-oncogene appears to be restricted to cells in the early stages of development, such as embryonal carcinoma (EC) cells. When EC cells are induced to differentiate, K-fgf expression is drastically repressed. To identify cis-acting DNA elements responsible for this type of regulation, we constructed a plasmid in which cat gene expression was driven by about 1 kilobase of upstream K-fgf human DNA sequences, including the putative promoter, and transfected it into undifferentiated F9 EC cells or HeLa cells as prototypes of cells which express or do not express, respectively, the K-fgf proto-oncogene. This plasmid was essentially inactive in both cell types, and the addition of more than 8 kilobases of DNA sequences upstream of the K-fgf promoter did not lead to any increase in chloramphenicol acetyltransferase (CAT) expression. On the other hand, when we inserted in this plasmid DNA sequences which are 3' of the human K-fgf coding sequences, we could detect a significant stimulation of CAT activity. Analysis of these sequences led to the identification of enhancerlike DNA elements which are part of the 3' noncoding region of K-fgf exon 3 and promote CAT expression only in undifferentiated mouse F9 or human NT2/D1 EC cells, but not in HeLa, 3T3, or differentiated F9 cells, therefore mimicking the physiological expression of the K-fgf proto-oncogene. Similar elements are also present in the 3' region of the murine K-fgf proto-oncogene, in a region showing high homology to the human K-fgf sequences. These regulatory elements can promote CAT expression from heterologous promoters in an EC-specific manner, suggesting that they interact with a specific cellular transacting protein(s) whose expression is developmentally regulated.